Metaphors in texts about climate change - Alice Deignan (Asociación Europea de Lenguas para Fines Específicos, 2017)
This article discusses the use of metaphors and metonyms in texts about climate change in different registers, with a particular focus on the information given to young people, and what they understand about the topic. It begins by considering the role of metaphorical thinking and language in science, and reviews some of the work on scientific metaphor in expert and popular genres. The article analyses the different functions of metaphors in two texts about anthropogenic climate change from different genres, arguing that in the popular text analysed metaphors tend to have the function of entertaining and dramatizing, and introducing and concluding (interpersonal and textual), as opposed to their informational (ideational) function in the research article that was analysed. I then discuss a corpus and discourse analysis of young people’s talk about climate change. The young people’s use of figurative language is compared with that of researchers and educationalists. The analysis finds that, consistent with work on scientific popularisations, written texts for non-specialists tend to “open up” in Knudsen’s (2003) terms experts’ metaphors, extending them creatively. I found that on occasion this seems to lead to, or reflect, misunderstandings of the underlying science. I also find that young people reference Arctic and Antarctic animals as symbols of the problem of climate change.